Menghargai Peran Guru: Tantangan dan Solusi dalam Mewujudkan Lingkungan Pendidikan yang Beretika - Annisa Salma Nabila; Rama Mahesa; Rintan Agustiani; Rosnada Asmahan; Syifa Adella; Siti Komariah; Muhammad Retsa Rizaldi Mujayapura (Jurnal Sosiologi Pendidikan Kolaboratif, 2025)
Students' disrespect for teachers is one of the big challenges in the world of modern education. This phenomenon can be seen in one of the private high schools in Bandung, where students tend to disrespect teachers, consider teachers only as providers of educational services, and show disrespectful behavior during the teaching and learning process. This problem has an impact on disrupting a conducive learning atmosphere and decreasing teacher enthusiasm for teaching. This research aims to analyze the factors that influence students' disrespect for teachers and find strategic solutions to rebuild the value given to teachers. The method used is a qualitative approach with participant observation techniques, in-depth interviews and document analysis. The research results show that students' disrespect is influenced by several factors, such as parental parenting patterns, the negative influence of social media, and weak character education in schools. This disrespect causes disruption to the ideal learning process. However, this research also found that building positive emotional relationships between teachers and students can be an effective strategy in creating an ethical learning environment.